Rituximab is more effective than second anti-TNF therapy in rheumatoid arthritis patients and previous TNFα blocker failure - Kekow J (Dove Medical Press, 2012)
Joern Kekow,1 Ulf Mueller-Ladner,2 Hendrik Schulze-Koops31Clinic of Rheumatology and Orthopedics, Otto-von-Guericke University of Magdeburg, Vogelsang-Gommern; 2Department of Rheumatology and Clinical Immunology, Kerckhoff Clinic, Bad Nauheim; 3Division of Rheumatology, University of Munich, Munich, GermanyPurpose: To assess the efficacy of one course of rituximab (two 1-g doses) compared to an alternative tumor necrosis factor-α (TNFα) blocker in rheumatoid arthritis patients who had experienced one previous TNFα blocker failure (eg, etanercept, adalimumab, or infliximab).Patients and methods: The efficacy of both treatments was studied in this retrospective, multicenter, noninterventional cohort study with 196 patients. All patients had active rheumatoid arthritis defined by a Disease Activity Score-28 of ≥3.2 despite having TNFα blocker therapy, and were followed over 6.6 months on average after switching to rituximab versus a second TNFα blocker (ie, switching to etanercept, adalimumab, or infliximab) at baseline.Results: At baseline, both cohorts showed similar demographic and disease-related characteristics (including Disease Activity Score-28). At the end of observation, mean Disease Activity Score-28 was significantly lower after treatment with rituximab than with a second TNFα blocker (-1.64 [95% confidence interval: -1.92; -1.36] versus -1.19 [95% confidence interval: -1.42; -0.96], P = 0.013). This difference between the two groups was even more pronounced when patients were seropositive for rheumatoid factor (-1.66 versus -1.17, P = 0.018) and anti-cyclic citrullinated peptide antibodies (-1.75 versus -1.06, P = 0.002). More rituximab-treated patients achieved good European League Against Rheumatism response than TNFα blocker-treated patients (30% versus 15%), and less patients were nonresponders (22% versus 35%) according to European League Against Rheumatism criteria (P = 0.022, chi-squared test).Conclusion: Treatment with rituximab was more effective than a second TNFα blocker therapy in rheumatoid arthritis patients after failure of the first TNFα blocker. It was found that anti-cyclic citrullinated peptide antibodies may be a useful predictive biomarker for response to rituximab in patients with TNFα blocker treatment failure.Keywords: rheumatoid arthritis, rituximab, anti-cyclic citrullinated peptide antibodies, rheumatoid factor